The Role of Government in Driving Sustainability: A Public Policy Perceptive - Jawahitha Sarabdeen (Ital Publication, 2024)
Sustainability is defined as socio-economic accomplishment without compromising the natural environment. The objective of the research is to assess the role of the government in driving sustainability as explained in the UN Sustainability Development Goals (SDGs). The research used content analysis and survey methods to understand the critical role of the government in achieving sustainable development and the perceptions of Saudi Arabian residents in this regard. The findings of the content analysis showed that the role of government at all levels is important to achieving sustainable development. The survey results also support the findings of the content analysis and show that the government's role in attaining sustainability is significant. All the variables of sustainability about government role proved to be very important. The research provided appropriate policy and practical implementation to facilitate the achievement of sustainability. The policy implications are that the government at all levels needs to ensure appropriate laws, regulations, codes, and the adoption of those rules to drive sustainable development. They also ensure that they have allocated resources to achieve sustainable development. In practical terms, the government should devise strategies for all levels of government to drive sustainable development. It should also set up participatory frameworks to ensure increased public involvement in urban planning and introduce education and public campaigns. Doi: 10.28991/ESJ-2024-08-03-023 Full Text: PDF